Evaluating the effectiveness of speed humps and rumble strips in improving pedestrian safety in Addis Ababa, Ethiopia - Getu Segni Tulu; Robert Tama Lisinge; Abrham Gebre Tarekegn; Tigist Eshetu (PLoS ONE, 2025)
Pedestrian fatalities remain a major road safety problem in Addis Ababa. To address this problem, speed humps and rumble strips were introduced on high-crash road segments in the city in 2017. As a case study that can be useful elsewhere, the aim of this research is to evaluate the effectiveness of speed hump with rumble strips in Addis Ababa. This study uses descriptive and inferential statistics to evaluate the impact of these interventions. Crash data between 2014 and 2021, excluding 2017 when the measures were implemented, is used in the analysis. The interventions led to a 25.08% reduction in operating speeds, with statistically significant speed reductions for passenger cars. Our findings on the extent to which speed humps and rumble strips lowered the speed of buses and trucks are not conclusive. Notable speed drops were observed at humps in some road segments while humps had no appreciable effect on speed in others. This underscores the need for additional measures or other approaches to reduce the operating speed of buses and trucks. The equivalent crash number for pedestrian crashes reduced by 24.45% and total crashes dropped by 51.14%. While crashes involving pedestrians crossing roads reduced, those involving pedestrians walking along travel lanes increased by 15.94%. These mixed results suggests that the effectiveness of speed humps and rumble strips depends on the type of crash being addressed and the category of vehicle involved.